2016
DOI: 10.1097/psy.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anxiety on Caloric Intake and Satiety-Related Brain Activation in Women and Men

Abstract: OBJECTIVE To test the relationship of anxiety to caloric intake and food cue perception in women and men. METHODS Fifty-five twins (26 complete, 3 incomplete pairs; 51% women) underwent 2 functional magnetic resonance imaging (fMRI) scans (before and after a standardized meal) and then ate at an ad libitum buffet to objectively assess food intake. State and trait anxiety were assessed using the State-Trait Anxiety Inventory. During the fMRI scans, participants viewed blocks of fattening and non-fattening foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
2
13
1
Order By: Relevance
“…In particular, anxiety tendency was statistically significant only for potato chips. This finding is in line with eating behaviour literature in which higher scores of the anxiety trait were positively associated with hypercaloric food consumption [ 26 , 27 ]. However, when nutritional claims were considered as attributes in the food choice of this hedonic food product, we found a positive willingness to pay for reduced-fat, low-salt potato chips, and a negative willingness to pay for potato chips bearing both nutritional claims.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, anxiety tendency was statistically significant only for potato chips. This finding is in line with eating behaviour literature in which higher scores of the anxiety trait were positively associated with hypercaloric food consumption [ 26 , 27 ]. However, when nutritional claims were considered as attributes in the food choice of this hedonic food product, we found a positive willingness to pay for reduced-fat, low-salt potato chips, and a negative willingness to pay for potato chips bearing both nutritional claims.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the differences in purchase behaviour between utilitarian and hedonic food products with NCs might also be influenced by personal and psychological factors. These factors have been extensively addressed in the literature on eating behaviour, such as body image [ 21 , 22 , 23 ], emotional eating style [ 24 , 25 ], and anxiety tendency [ 26 , 27 ], which could be strongly related to consumer shopping behaviour. To illustrate, some studies showed that certain individuals react to external stimuli by increasing their consumption of indulgent food products (i.e., energy-dense food product) as a coping strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that the interpretation of Prevotella in the gut could depend on the concentration of other bacterial species that are co-habitating the intestine. Lastly, because of the bidirectional communication between the gut and the brain, we can't discard the possibility of anxiety regulating food consumption [103] and therefore gut microbiome composition through nutrient availability. In this case the relationship between Prevotella and anxiety would not be a causative.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical experiments or commonly-used behavioral tests, especially in the field of brain and behavior, female animals have often been omitted deliberately due to their own estrous cycle. [20][21][22] This limited application of females in behavioral experiments, the study on the anxiolytic activity of EOs, for instance, thus results in the presence of sexually dimorphic patterns of prevalence and/or severity, 22) as well as the lack of systematic studies on the underlying mechanism of anxiety behaviors. 20,23,24) The main objective of the present study was to evaluate the anxiolytic effect of cedrol on female ICR mice via the elevated plus maze (EPM) and light-dark box (LDB) paradigm.…”
Section: Introductionmentioning
confidence: 99%